Voltammetric determination of aluminium(III) at tannic acid capped-gold nanoparticle modified electrodes - Suherman, A; Tanner, E; Kuss, S; Sokolov, S; Holter, J; Young, N; Compton, R (Elsevier, 2018)
The contamination of drinking water and food products by aluminium represents a serious health issue, as it is associated with chronic neurodegenerative diseases. Herein we report an analytical electrochemical method for the determination of aluminium(III) at glassy carbon electrodes, modified with commercially available tannic acid-capped gold nanoparticles. The combination of gold nanoparticles and tannic acid as capping/chelating agent results in an accurate and sensitive detection of aluminium(III) in aqueous solutions by square wave voltammetry (SWV). Employing the presented methodology, clear measurable signals are seen even at the low limit of 10.0 pM, markedly and usefully lower than the permissible level of 7.4 μM for drinking water as defined by the WHO and which compares favourably with alternative detection methods.